Perencanaan dan Perancangan Wisata Edukasi Pertanian di Kota Denpasar - I Dewa Gede Purnama Wara Nugraha; Made Suryanatha Prabawa; I Kadek Merta Wijaya (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Denpasar City is the capital city of Bali Province, apart from being the capital city of Bali Province, it is also the center of various activities in Bali Province which resulted in the rate of population growth becoming uncontrollable. As a result of the uncontrolled growth rate of agricultural land, the impact of this growth rate is that agricultural land in Denpasar City is decreasing, the highest reduction of agricultural land is in South Denpasar Regency. Given the need for Agricultural Education Tours in Denpasar City to provide education about the importance of managing agricultural land as a source of food for daily life, this agricultural educational tour provides new knowledge for visitors about management from seedling to harvesting, besides that this educational tour aims to provide a sense of empathy for children, youth and adults about the importance of maintaining the remaining agricultural land and utilizing the existing land as a place of development both inside the house and around the house. This educational tourism location is located on Jalan Tukad Balian Renon using the basic concept of â€œsustainable energyâ€ and the design theme of â€œeco-architectureâ€.